ACTIVATION OF HUMAN BLOOD MONONUCLEARS BY LIPOPOLYSACCHARIDE OF DIFFERENT COMPOSITION - S. V. Zubova; E. V. Voloshina; N. I. Kosjakova; S. V. Grachev; I. R Prokhorenko (Медицинская иммунология, 2014)
Influence of lipopolysaccharide (LPS) composition upon activation of human blood mononuclears was investigated, by measuring levels of pro-inflammatory TNFα and IL-6 cytokines released by the cells. It is shown that LPS from Rhodobacter capsulatus PG, in contrast to E. coli LPS, did not activate the target cells for synthesis of the cytokines.